Cementing of the hip arthroplasty stem increases load-to-failure force: a cadaveric study - Klasan, Antonio; Bäumlein, Martin; Bliemel, Christopher; Putnis, Sven Edward; Neri, Thomas; Schofer, Markus Dietmar; Heyse, Thomas Jan (Acta Orthopaedica, 2019)
Background and purpose — To date, there is not a single clinical or mechanical study directly comparing a cemented and a cementless version of the same stem. We investigated the load-to-failure force of a cementless and a cemented version of a double tapered stem. Material and methods — 10 femurs from 5 human cadaveric specimens, mean age 74 years (68–79) were extracted. Bone mineral density (BMD) was measured using peripheral quantitative computed tomography. None of the specimens had a compromised quality (average T value 0.0, –1.0 to 1.4). Each specimen from a pair randomly received a cemented or a cementless version of the same stem. A material testing machine was used for lateral load-to-failure test of up to a maximal load of 5.0 kN. Results — Average load-to-failure of the cemented stem was 2.8 kN (2.3–3.2) and 2.2 kN (1.8–2.8) for the cementless stem (p = 0.002). The cemented version of the stem sustained a higher load than its cementless counterpart in all cases. Failure force was not statistically significantly correlated to BMD (p = 0.07). Interpretation — Implanting a cemented version of the stem increases the load-to-failure force by 25%.